Nitric oxide in paediatric respiratory disorders: novel interventions to address associated vascular phenomena?. (August 2016) - Akter, Farhana; Coghlan, Gerry; de Mel, Achala
Nitric oxide (NO) has a significant role in modulating the respiratory system and is being exploited therapeutically. Neonatal respiratory failure can affect around 2% of all live births and is responsible for over one third of all neonatal mortality. Current treatment method with inhaled NO (iNO) has demonstrated great benefits to patients with persistent pulmonary hypertension, bronchopulmonary dysplasia and neonatal respiratory distress syndrome. However, it is not without its drawbacks, which include the need for patients to be attached to mechanical ventilators. Notably, there is also a lack of identification of subgroups amongst abovementioned patients, and homogeneity in powered studies associated with iNO, which is one of the limitations. There are significant developments in drug delivery methods and there is a need to look at alternative or supplementary methods of NO delivery that could reduce current concerns. The addition of NO-independent activators and stimulators, or drugs such as prostaglandins to work in synergy with NO donors might be beneficial. It is of interest to consider such delivery methods within the respiratory system, where controlled release of NO can be introduced whilst minimizing the production of harmful byproducts. This article reviews current therapeutic application of iNO and the state-of-the-art technology methods for sustained delivery of NO that may be adapted and developed to address respiratory disorders. We envisage this perspective would prompt active investigation of such systems for their potential clinical benefit.